EFFECT OF VACUUM RESIDUE AND PETROLEUM BENZINE AS THE ADDITIVE CALORIFIC VALUE AND MOISTURE OF COAL - Ezra Bella Ramadhani Putri; Wahyudi Zahar; Lenny Marlinda (Puslitbang tekMIRA, 2022)
Upgrading the coal is a process that increases the calorific value of low-rank coal through decreasing the moisture content of the coal. This method usually uses mixed heavy oil to close the opened pores after coal upgrading. The additives have a molecule structure like heavy oil. The aim of this study is to determine the effect of additives on the moisture content and calorific value after coal upgrading process. Coal upgrading in this study applies several variations i.e., coal particle size and coal mass mixed with an additive which is a mixture of vacuum residue and petroleum benzine with a ratio of 0.005 g: 1 mL as a coater. Before upgrading process, the moisture content and calorific value of the coal is 13.39 %adb and 6,663 cal/g db. After the process, the lowest moisture content of the coal in the ratio of coal (b/v) and additives was 4:3 with 21.75% ad. The highest calorific value of the coal was shown in the ratio of coal (b/v) and additives 1:1 with 7,189 kcal/kg. The lowest moisture content is indicated by the particle size of -120 mesh. The highest calorific value of coal is shown by the particle size of -120 mesh.